Ideologi Penerjemahan Lirik Lagu: Film Frozen dan Frozen 2 dari Bahasa Inggris ke dalam Bahasa Prancis - Davina, Florencia Lorraine; Mardalena, Ismirani (Kementerian Sekretariat Negara Republik Indonesia, 2022)
Song lyrics translation is a common thing to do. There have been many articles about song lyrics, including film soundtracks like Disney’s animations. This article aims to explain and find the ideology of the song lyrics in Disney’s musical animation Frozen and Frozen 2. In each film, three songs are chosen based on the most listened-to songs on Spotify. The method used is data collection in qualitative research. Each song is divided by verse and categorized by its translation strategy. Then, the author explains the problems found in each verse and the purpose of using said translation strategy. Lefevere’s (1975) translation strategies are used to identify the song lyrics’ translation strategies and Venuti’s theories to identify the ideology. From a total of 42 analyzed verses, it is found that the translator’s ideology tends to show domestication, which can be clearly seen in their dominant use of expressions, metaphors, and vocabularies commonly used in the target language. Keywords: translation ideology, Lefevere’s poetry translation strategies, film soundtrack, Frozen, Disney animation